Kuwalitas Produk dan Harga Terhadap Kepuasan Pemakai Handphone Nokia - Basyth, Abdul; Fitriya, Fitriya (Universitas muhammadiyah palembang, 2011)
Information technology is developing rapidly in recent years. As a result of the rapid development of information technology cummunication tools have grown rapidly as well. One brand of communication tools that indonesia consumer market is Nokia. This study wanted to find out wheter the product quality and price influence on constomer satispaction. Sample of 100 respondents used student faculty of Economics University of Muhammadiyah Palembang. The data was obtained by distributing questionnaires to the respondent directly. Analysis tools used in this study where factor analysis. The result showed that after being that a reliable , features, from, durability and service. While the secound component there are 4 new variable namely durability, purchase price,pride, and service. Overall the dimensions of the product and the price has a positive impact on customer satisfaction